Peningkatan Fungsi Atensi dan Memori Jangka Pendek pada Wanita Dewasa Muda dengan Ansietas setelah Terapi Mewarnai - Moses A Krisnanda; Stella T Hasianna; Yenni Limyati (Journal of Medicine and Health, 2020)
Attention and memory are influenced by anxiety. This study aimed to analyze the effect of coloring therapy on the improvement of attention and short-term memory function in young adult women with anxiety. The analytic quasi-experimental method was used with pre-test and post-test design. The measured data were attention (Stroop test score) and short-term memory (Scenery Picture Memory Test / SPMT score). The subjects were 25 female university students with anxiety (Depression Anxiety Stress Scale / DASS-42 score ?8). This study showed the mean Stroop test scores of pre-test and post-test were 136.20 and 72.60 seconds subsequently, and the mean SPMT scores of pre-test and post-test were 17.88 and 20.92 subsequently. Wilcoxon's statistical analysis test with ?=0.05 showed a p-value of 0.000 for both the Stroop test and SPMT score (highly significant). We concluded that coloring therapy improved attention and short-term memory function in young adult women with anxiety. Keywords: coloring therapy, attention, short-term memory, cognitive, anxiety